A cause and effect of a nonpayment model based on the DEMATEL algorithm - Lee, Chia Kuang; Bujna, Marián; Ahmad Huzaimi, Abd Jamil; Ee, Pei Theng (American Society of Civil Engineers (ASCE), 2023)
Payment is regarded to be the construction industry’s lifeblood. Late and nonpayment concerns have plagued the construction industry. Previous research has only looked at the cause and effect of payment problems in the construction industry, not the link between the variables. The purpose of this study is to look at the causes and repercussions of nonpayment, as well as their interactions. The study’s list of causes and consequences was compiled from a literature review, and nine were retrieved. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique was used to create a causal relationship between the causes and effects of nonpayment so they may be understood and intervened in. Paymaster’s inadequate financial management (C1), local culture and attitude (C2), document error (C6), contractual provision (C8), and disagreement on the valuation of work done (C9) are the major cause factors, according to the data collected from 13 respondents. The key repercussions, on the other hand, include cash flow problem (E2), bankruptcy and liquidation (E4), project abandonment (E5), delay (E7), and disputes (E8). The conclusions of this study can assist major players in the construction sector, as well as the government, in establishing a strategy to effectively address the nonpayment problem in the industry